2012
DOI: 10.1111/j.1440-1746.2011.06894.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral hepatocyte growth factor gene mediated by attenuated salmonella on 2‐, 4‐, 6‐trinitro‐benzene‐sulfonic‐acid‐induced ulcerative colitis in rat

Abstract: TPH inhibits the proliferation of T lymphocytes and the antibody production of B lymphocytes. Furthermore, it ameliorates mucosal inflammation and promotes the regeneration of mucosa and the healing of the colonic ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Compared with the DSS model group, Eckol treatment decreased the number of CD4 + T cells, but increased the number of CD8 + T cells in the colonic tissues, suggesting that Eckol might contribute to inhibited CD4 + T-cell responses and enhanced CD8 + T-cell responses, resulting in an immunosuppressive micro-environment in chronic UC colons. Experimental evidence has shown that considerable ant-colitis agents or therapeutics reduced the ratio of CD4 + and CD8 + T lymphocytes in colonic tissues to maintain intestinal immune homeostasis, thereby helping to attenuate the progression of UC [39][40][41][42]. Similarly, our results demonstrate that Eckol increased CD11c + DCs and meanwhile decreased the ratio of CD4 + to CD8 + T cells, which might indicate the regulatory effect of Eckol on intestinal immune tolerance.…”
Section: Possible Involvement Of Toll-like Receptor 4 (Tlr4) Pathwaysupporting
confidence: 70%
See 1 more Smart Citation
“…Compared with the DSS model group, Eckol treatment decreased the number of CD4 + T cells, but increased the number of CD8 + T cells in the colonic tissues, suggesting that Eckol might contribute to inhibited CD4 + T-cell responses and enhanced CD8 + T-cell responses, resulting in an immunosuppressive micro-environment in chronic UC colons. Experimental evidence has shown that considerable ant-colitis agents or therapeutics reduced the ratio of CD4 + and CD8 + T lymphocytes in colonic tissues to maintain intestinal immune homeostasis, thereby helping to attenuate the progression of UC [39][40][41][42]. Similarly, our results demonstrate that Eckol increased CD11c + DCs and meanwhile decreased the ratio of CD4 + to CD8 + T cells, which might indicate the regulatory effect of Eckol on intestinal immune tolerance.…”
Section: Possible Involvement Of Toll-like Receptor 4 (Tlr4) Pathwaysupporting
confidence: 70%
“…Mar. Drugs 2023, 21, 376 7 shown that considerable ant-colitis agents or therapeutics reduced the ratio of CD4 CD8 + T lymphocytes in colonic tissues to maintain intestinal immune homeos thereby helping to attenuate the progression of UC [39][40][41][42]. Similarly, our results dem strate that Eckol increased CD11c + DCs and meanwhile decreased the ratio of CD CD8 + T cells, which might indicate the regulatory effect of Eckol on intestinal imm tolerance.…”
Section: Eckol Modulated the Infiltration Of Immune Cells In Dss-chal...supporting
confidence: 63%
“…Some reports showed the increase of CD4 + T counts and CD4 + /CD8 + ratio indicates the aggravation of UC [ 19 ]. Meanwhile, the downregulation of accumulation of CD4 + and CD8 + can ameliorate the inflammation and colonic tissue damage [ 20 ].…”
Section: Introductionmentioning
confidence: 99%